Cultivating a Growth Mindset: HR's Role in Fostering Continuous Learning Cultures - Novrianto, Andry; Fitriadi, Yohan; Nengsi, Neni Sri Wahyuni (Equator Journal of Management and Entrepreneurship (EJME), 2024)
This study investigates the dynamics of Growth Mindset, HR's Role, Engagement or Employee Participation, and Continuous Learning Cultures within PT. Teluk Luas. Using quantitative methods and Structural Equation Modeling (SEM) with Smart PLS, the research explores direct and indirect relationships among these variables. The findings reveal that Growth Mindset significantly influences Engagement or Employee Participation and Continuous Learning Cultures, emphasizing the role of a growth-oriented mindset in fostering employee engagement and a culture of continuous learning. Additionally, while HR's Role directly affects Engagement or Employee Participation but not Continuous Learning Cultures, its significant indirect effect on Continuous Learning Cultures through Engagement or Employee Participation underscores the pivotal role of HR in enhancing engagement, thereby contributing to a conducive environment for continuous learning. These insights provide valuable implications for organizational strategies aimed at cultivating a dynamic and learning-oriented workplace culture.